Extending the concept of research impact literacy: levels of literacy, institutional role and ethical considerations [version 2; peer review: 2 approved] - David Phipps; Julie Bayley (Emerald Publishing, 2019)
Building on the concept of 'impact literacy' established in a previous paper from Bayley and Phipps, here we extend the principles of impact literacy in light of further insights into sector practice. More specifically, we focus on three additions needed in response to the sector-wide growth of impact: (1) differential levels of impact literacy; (2) institutional impact literacy and environment for impact; and (3) issues of ethics and values in research impact. This paper invites the sector to consider the relevance of all dimensions in establishing, maintaining and strengthening impact within the research landscape. We explore implications for individual professional development, institutional capacity building and ethical collaboration to maximise societal benefit.